1992
DOI: 10.1161/01.cir.86.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Long-term predictors of subsequent cardiovascular events with coronary artery disease and 'desirable' levels of plasma total cholesterol.

Abstract: Low HDL-C (or high TC:HDL-C) is strongly predictive of subsequent cardiovascular events in subjects with CAD, despite desirable TC. As such, identification of this potentially modifiable risk factor should be actively pursued in this high-risk subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…PI may also have direct value in CAD patients with reduced HDL-C but normal total cholesterol levels, in whom the risk of recurrent cardiovascular events is doubled (27,28). Therefore, future studies are required to examine the effects of PI in patients with low HDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…PI may also have direct value in CAD patients with reduced HDL-C but normal total cholesterol levels, in whom the risk of recurrent cardiovascular events is doubled (27,28). Therefore, future studies are required to examine the effects of PI in patients with low HDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al 29 demonstrated the significance of low HDL-C as risk factor on the incidence of recurrent cardiovascular events in a follow-up study of patients with angiographically proven CAD and desirable TC levels. The AFCAPS/TexCAPS study 3 showed that, in a population without a history of CAD and with normal TC and LDL-C levels, a below-average HDL-C level (0.94 mmol/L for men and 1.03 mmol/L for women) forms an important risk factor for a first major coronary event.…”
Section: Hdl Metabolism and Recurrent Cardiovascular Eventsmentioning
confidence: 99%
“…9 -11 Previous studies from our laboratory have shown that subjects with isolated low HDL cholesterol were neither characterized by hyperinsulinemia nor by visceral obesity. 12 Although studies have suggested that patients with isolated low HDL cholesterol syndrome may be at increased CHD risk, 9,10,13,14 it appears very difficult to increase HDL cholesterol levels in these individuals by diet, weight loss, or pharmacotherapy. 15 …”
mentioning
confidence: 99%